PO027 Spontaneous cervical epidural haematoma presenting as thunderclap headache – case presentation. (1st December 2017) - Wysota, Barbara; Williams, Adrian; Hayton, Tom
Abstract : Thunderclap headache is most commonly associated with subarachnoid haemorrhage or other acute intracranial pathology. It's typically investigated with head imaging and lumbar puncture. We are presenting here the case of spontaneous cervical epidural haematoma manifesting as thunderclap headache. This pathology could be missed by following standard investigations of thunderclap headache and highlighting importance of through clinical history. 86 year old man presented to Emergency Department with thunderclap headache and loss of consciousness. Patient developed severe occipital headache while leaving the bath than lost consciousness. After waking up he was unable to stand up, his lower legs felt numb and weak. Headache gradually improved within 30 min. His CT head after arrival to A and E didn't show any acute intracranial pathology. CSF was normal, xantochromia was negative. Within 48 hours patient recovered almost completely. Was able to mobilise independently and was considered fit for discharge by medical team. After neurology review MRI scan of cervical spine was organised revealing spontaneous cervical epidural haematoma.